Comparison of Costs and Income of Farming Businesses Rice Fields That Use Harvesting Machines Combine Harvester with Power Thresher (Case in Karanganyar Village, Kandanghaur District, Indramayu Regency) - Winarti Yeha, Meylina Fajar; Khaerudin, Urip; Purnomo, Dwi (Jurnal Impresi Indonesia, 2025)
Agricultural mechanization, such as combine harvesters (CH) and power threshers (PT), is critical to addressing labor shortages and improving rice farming efficiency in Indonesia. This study compares the costs, income, and feasibility of CH and PT in Karanganyar Village, Indramayu. A quantitative approach with purposive sampling (40 farmers) was used, employing income analysis and paired t-tests (SPSS 26). CH reduced total costs by Rp3.36 million/ha (Rp22.28 million vs. PT’s Rp25.64 million) and increased net income by Rp5.88 million/ha (Rp12.60 million vs. PT’s Rp6.72 million), with a higher R/C ratio (1.57 vs. 1.26). Statistical analysis confirmed significant differences (Sig. 0.000). CH enhances profitability by cutting labor costs and minimizing post-harvest losses, supporting its adoption for sustainable rice farming. Policymakers should promote CH through subsidies and training.